1988
DOI: 10.1002/ajmg.1320300111
|View full text |Cite
|
Sign up to set email alerts
|

Fragile X syndrome: Growth, development, and intellectual function

Abstract: We collected data on growth, psychomotor development, speech and language development, and intellectual function on a cohort of 100 males with the fragile X chromosome and 95 carrier females. The data include information on prenatal growth (33 males), growth during the preadult years (32 males), psychomotor development during the first 2 years (25 males), speech and language development (15 males and 5 females), and intellectual function (93 males, 33 females, and 10 obligate carriers who were cytogenetically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 28 publications
5
24
0
Order By: Relevance
“…85,86 After birth, the head circumference tends to rise above the 50th percentile and continues to be larger than for male patients without FXS. 75,77,80,82,83,87 This is also reflected in the FXCRC data, where a larger head circumference was similar to that in other studies of adults with FXS. 75,87 For girls, Hagerman et al (1992) 88 found no difference in height, weight, or head circumferences of girls with FXS compared with relatives negative for the full mutation.…”
Section: Growthsupporting
confidence: 85%
See 1 more Smart Citation
“…85,86 After birth, the head circumference tends to rise above the 50th percentile and continues to be larger than for male patients without FXS. 75,77,80,82,83,87 This is also reflected in the FXCRC data, where a larger head circumference was similar to that in other studies of adults with FXS. 75,87 For girls, Hagerman et al (1992) 88 found no difference in height, weight, or head circumferences of girls with FXS compared with relatives negative for the full mutation.…”
Section: Growthsupporting
confidence: 85%
“…However, the overall proportion of infants with low birth weight was similar to that in the general population. The mean head circumference 80,81 and mean birth length 77,78,80,81 were not different from those of control populations.…”
Section: Growthmentioning
confidence: 65%
“…Jacobs et al [1980] also reported an association of IQ with proportion of fra(X) cells but re-examination of their data by Turner and Jacobs [1983] found no correlation of frequency of expression and IQ. Recently, however, Prouty et al [1988] observed an inverse relationship between IQ and frequency of expression among females.…”
Section: Introductionmentioning
confidence: 93%
“…After birth, the head circumference tends to rise above the 50 th percentile and continues to be larger than those without FXS. Jacobs et al noted that in six of nine affected men, the head circumference was greater than the 90 th percentile (18), but other studies have shown that the mean head circumference (19)(20)(21) and the mean birth length are not different of those of control population (21). Hagerman and colleagues found no difference in the height, weight or head circumference of girls with FXS compared with those without the full mutation (22).…”
Section: After Birth Problemsmentioning
confidence: 99%